The importance of monitoring nurses' workplace satisfaction of nurses for the well-being of all employees in nursing - Lorber, Mateja (Obzornik zdravstvene nege, 2015)
Introduction: Work is an important constituent of an individual%s life since the experience of work influences well-being and health. The well-being of employees is an important issue in the work environment. The aim was to examine the relationship between satisfaction in the workplace and the well-being of employees in nursing. Methods: Quantitative research based on a cross-sectional study was used, with 640 employees in nursing from eight Slovenian hospitals participating in the study. A structured survey questionnaire was administered. The relationship between psychological well-being and workplace satisfaction was analysed with correlation and linear regression analysis. Results: The workplace satisfaction (x = 3.69, s = 1.13) and well-being ( x=161.27, s = 55.19) of employees in nursing are at a middle level. With the correlation analysis we established that well-being statistically significantly correlates with workplace satisfaction (r = 0.611, p < 0.001). Workplace satisfaction explains 42 % of the total variability of well-being of employees in nursing. Discussion and conclusion: It is necessary for every health care organization to take care of its employees' workplace satisfaction and well-being. Health care organizations can be successful and achieve their organisational objectives if their employees are satisfied with their work and have a high level of well-being.
Keywords: delo; dobro počutje; medicinske sestre; nurses; satisfaction; well-being; work; zadovoljstvo